106 Which virtual histology intravascular ultrasound properties discriminate better between stable angina pectoris and troponin positive acute coronary syndrome: assessment of plaques or analysis of the whole coronary artery vasculature?. (22nd September 2015) - Calvert, P A; Obaid, D R; West, N E J; Shapiro, L M; McNab, D; Densem, C G; Schofield, P M; Braganza, D; Clarke, S C; O'Sullivan, M; Ray, K R; Bennett, M R
Abstract : Introduction: Previous work has examined the relationship between plaque virtual-histology intravascular ultrasound (VH-IVUS) appearances (local coronary factors) and patient presentation. However, little is known about the relationship between patient presentation and VH-IVUS appearances of the whole coronary vascular tree (global coronary factors), which may be a better 'barometer' of patients' cardiovascular risk. This study aims to determine which VH-IVUS coronary factors, local or global, discriminate better between stable angina and troponin-positive acute coronary syndrome (ACS). Methods: This 200 patient cross-sectional study examined the VH-IVUS appearances of the whole coronary vascular tree (full 3-vessel VH-IVUS) in patients referred for percutaneous coronary intervention (PCI) with either stable angina or ACS. VH-IVUS imaging preceded PCI. Results are presented as mean±SD unless stated. Results: There were no differences in baseline demographics between stable angina and ACS groups including age, sex, blood pressure, previous MI, diabetes, serum cholesterol/HDL ratio and smoking. On full 3-vessel VH-IVUS, diabetic patients had a greater necrotic core volume (238±168 mm 3 vs 120±77 mm 3, p=0.022) and plaque burden (1673±645 mm 3 vs 1102±445 mm 3, p=0.006) than non-diabetics. After adjusting for total plaque volume, diabetics still had more necrotic core volume than non-diabetics: 12.9±5.0% vs 10.3±4.1%, p=0.045. Full 3-vessel VH-IVUS necrotic core volume did not differ between stable angina and ACS groups, even after adjusting for total plaque volume: 10.1±4.0% vs 11.6±4.6%, p=0.10, indicating that plaque composition throughout the whole arterial tree could not predict presentation. However, ACS patients were more likely to have at least one VH-IVUS derived thin-capped fibroatheroma (ID-TCFA) in the target vessel than stable angina patients: OR 2.2 (95% CI 0.9 to 5.4), p=0.048. Abstract 106 Figure 1 shows ID-TCFA (FI=fibrous tissue, FF=fibrofatty tissue, NC=necrotic core, DC=dense calcium). Conclusion: Although global coronary factors (whole coronary artery plaque burden and necrotic core volume) may define high-risk patient populations such as diabetics, local plaque structure such as presence of ID-TCFAs in the target vessel may be more important in governing mode of patient presentation.